Percutaneous Transhepatic Biliary Drainage for Malignant Biliary Obstruction in Advanced Solid Organ Malignancy: Clinical Outcomes and Quality of Life Perspective - Vaitiekunas, Laurence; Caird, Susan; Eriksen, David (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Malignant obstructive jaundice carries a poor prognosis. While percutaneous transhepatic biliary drainage (PTBD) offers a treatment option, its impact on quality of life remains unclear. This study aimed to assess the potential impact of PTBD on quality of life in patients with obstructive jaundice secondary to advanced malignancy, using surrogate markers such as complications, hospital length of stay, readmission, reintervention, and mortality. Materials and Methods: This retrospective analysis was conducted on a single-center cohort of all patients with advanced solid organ malignancies undergoing PTBD between April 2020 and February 2022. Data were collected from electronic medical records. Results: Among the 16 patients, 62.5% experienced abdominal pain and 37.5% developed cholangitis. Individual cases experienced peritonitis, biliary leak, perihepatic abscess, and hemobilia. The median hospital length of stay following PTBD was nine days. The 30-day readmission rate for PTBD-related complications was 31.3%, with a median of three total readmissions per patient. The 30-day reintervention rate was 62.5%. The 30-day all-cause mortality rate was 25% (95% CI: 8.9-53.3), including one procedure-related death. Conclusion: The high risk of complications, reinterventions, hospitalizations, and mortality associated with PTBD can negatively impact the quality of life of patients with obstructive jaundice secondary to advanced solid organ malignancies. Thorough patient assessments are crucial for selecting appropriate candidates for PTBD.